Al-Quran Literacy for Early Childhood with Storytelling Techniques - Dewi Mulyani; Imam Pamungkas; Dinar Nur Inten (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Muslim children are part of the Muslims. They are the successors and propagators of the da'wah of the Muslims. It is an obligation for parents and teachers to provide them with the ability to read, write and understand the Qur'an as a guide for the lives of Muslims. With the literacy of Al-Quran from an early age, it is expected the generations of Muslims to understand and literate the guidelines of his life. However, children are different from adults. Early childhood teachers should choose the right techniques for early childhood. Children love the sound playing, fun, and freedom from stress. In this case, is offered one of the techniques favored by early childhood, that is storytelling techniques. This research method descriptive analytic with a qualitative approach. So that's this method can produce a clearer picture of Al-Quran literacy strategies for early childhood. In operational research, researchers conduct interviews, observation literature studies. The results showed that 75% of children in group A enjoyed Quranic literacy with storytelling techniques and in group B children 41,6% liked it too. Thus Al-Quran literacy through storytelling techniques is a fun and meaningful activity.